Treatability of cheese whey for single-cell protein production in nonsterile systems: Part II. The application of aerobic sequencing batch reactor (aerobic SBR) to produce high biomass of Dioszegia sp. TISTR 5792 - Sarawut Monkoondee (2018)
© 2016, Copyright © Taylor & Francis Group, LLC. This study aimed to investigate the efficiency of an aerobic sequencing batch reactor (aerobic SBR) in a nonsterile system using the application of an experimental design via central composite design (CCD). The acidic whey obtained from lactic acid fermentation by immobilized Lactobacillus plantarum sp. TISTR 2265 was fed into the bioreactor of the aerobic SBR in an appropriate ratio between acidic whey and cheese whey to produce an acidic environment below 4.5 and then was used to support the growth of Dioszegia sp. TISTR 5792 by inhibiting bacterial contamination. At the optimal condition for a high yield of biomass production, the system was run with a hydraulic retention time (HRT) of 4 days, a solid retention time (SRT) of 8.22 days, and an acidic whey concentration of 80% feeding. The chemical oxygen demand (COD) decreased from 25,230 mg/L to 6,928 mg/L, which represented a COD removal of 72.15%. The yield of biomass production and lactose utilization by Dioszegia sp. TISTR 5792 were 13.14 g/L and 33.36%, respectively, with a long run of up to 180 cycles and the pH values of effluent were rose up to 8.32 without any pH adjustment.